Optical Glass and Optical Elements
A tailored glass composition with controlled components achieves a refractive index of 1.55 to 1.68 and high dispersion, addressing the limitations of existing glasses for chromatic aberration correction and optical system compactness.
Patent Information
- Application Number
- JP2021003357
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2041-01-13
AI Technical Summary
Existing optical glasses do not provide a refractive index in the range of 1.55 to 1.68 with high dispersion, limiting their utility in correcting chromatic aberration and making optical systems compact.
A specific glass composition is formulated with controlled amounts of B2O3, P2O5, Na2O, BaO, and other components to achieve a refractive index of 1.55 to 1.68 and high dispersion, ensuring excellent thermal stability and devitrification resistance.
The solution provides optical glasses with desired optical properties, including refractive index, Abbe number, and thermal stability, suitable for correcting chromatic aberration and enhancing optical system compactness.
Smart Images

Figure 0007606351000001 
Figure 0007606351000002 
Figure 0007606351000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical glass and an optical element. [Background technology]
[0002] Optical glass having a refractive index nd in the range of 1.55 to 1.68 and high dispersion is highly useful in correcting chromatic aberration in designing optical systems and making the optical system more compact and highly functional.
[0003] Patent documents 1 to 3 disclose optical glasses with a relatively low Abbe number νd. However, the optical glasses of Patent documents 1 to 3 have a large refractive index nd. Furthermore, when the optical constants of the optical glass disclosed in Patent document 4 were examined, it was found that the Abbe number νd was relatively low, but the refractive index nd was high. In other words, Patent documents 1 to 4 do not propose optical glasses with a refractive index nd in the range of 1.55 to 1.68 and high dispersion. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-74581 A [Patent Document 2] JP 2018-70414 A [Patent Document 3] International Publication No. 2013 / 031385 [Patent Document 4] Special Publication No. 2020-505311 Summary of the Invention [Problem to be solved by the invention]
[0005] It is therefore an object of the present invention to provide a high-dispersion optical glass having a refractive index nd in the range of 1.55 to 1.68, and an optical element made of said optical glass. [Means for solving the problem]
[0006] The gist of the present invention is as follows. (1) Contains B2O3 and K2O as glass components, The content of P2O5 is 35.0 to 60.0 mass%; The mass ratio of the B2O3 content to the P2O5 content [B2O3 / P2O5] is 0.39 or less; The NaO content is 5.0 to 40.0 mass%, The content of BaO is 15.0 mass% or less, The total content of MgO, CaO, SrO and BaO [MgO+CaO+SrO+BaO] is 18.0 mass% or less, The ZnO content is 15.0 mass% or less, The content of Nb2O5 is 25.0 mass% or less, The WO3 content is 5.0 mass% or less, The content of Bi2O3 is 10.0 mass% or less, The total content of TiO2, Nb2O5, WO3, Bi2O3 and Ta2O5 [TiO2+Nb2O5+WO3+Bi2O3+Ta2O5] is 3.0 to 30.0 mass%; An optical glass having a total content of TiO2, Nb2O5, WO3, Bi2O3, Ta2O5 and ZnO [TiO2+Nb2O5+WO3+Bi2O3+Ta2O5+ZnO] of 3.0 to 33.0 mass%.
[0007] (2) An optical element made of the optical glass described in (1) above. Effect of the Invention
[0008] According to the present invention, it is possible to provide a high-dispersion optical glass having a refractive index nd in the range of 1.55 to 1.68, and an optical element made of said optical glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In the present invention and this specification, the glass composition of optical glass is expressed on an oxide basis unless otherwise specified. Here, "glass composition on an oxide basis" refers to a glass composition obtained by converting the glass raw materials into oxides that exist in the optical glass after all of them are decomposed during melting, and each glass component is conventionally expressed as SiO2, TiO2, etc. The content and total content of glass components are on a mass basis unless otherwise specified, and "%" means "mass%".
[0010] The content of the glass component can be quantified by known methods, such as inductively coupled plasma atomic emission spectrometry (ICP-AES), inductively coupled plasma mass spectrometry (ICP-MS), etc. In this specification and the present invention, the content of a component being 0% means that the component is substantially not contained, and it is acceptable for the component to be contained at an unavoidable impurity level.
[0011] In this specification, unless otherwise specified, the refractive index refers to the refractive index nd at the d line of helium (wavelength 587.56 nm).
[0012] The Abbe number νd is used as a value representing the properties related to dispersion, and is expressed by the following formula: Here, nF is the refractive index at the F line (wavelength 486.13 nm) of blue hydrogen, and nC is the refractive index at the C line (656.27 nm) of red hydrogen. νd=(nd-1) / (nF-nC) (1)
[0013] The optical glass according to this embodiment will now be described in detail.
[0014] The optical glass according to this embodiment contains B2O3 as a glass component. The lower limit of the B2O3 content is preferably 0.3%, more preferably 0.6%, 0.8%, and 1.0%, in that order. The upper limit of the B2O3 content is preferably 15%, more preferably 13.0%, 11.0%, and 10.0%, in that order.
[0015] B2O3 is a glass network forming component and has the function of improving the thermal stability of glass. By setting the content of B2O3 within the above range, the thermal stability and devitrification resistance of glass can be improved. On the other hand, if the content of B2O3 is too high, the thermal stability and devitrification resistance of glass tend to decrease.
[0016] The optical glass according to this embodiment contains K2O as a glass component. The lower limit of the K2O content is preferably 3.0%, and more preferably 5.0%, 7.0%, 8.5%, 9.00%, and 9.20%, in that order. The upper limit of the K2O content is preferably 20.0%, and more preferably 17.0%, 15.0%, and 14.0%, in that order.
[0017] K2O has the function of improving the thermal stability and meltability of glass. By setting the content of K2O within the above range, an optical glass having excellent thermal stability and meltability can be obtained. On the other hand, if the content of K2O is too low, the thermal stability and meltability may decrease. Also, if the content of K2O is too high, the thermal stability may decrease.
[0018] In the optical glass according to this embodiment, the P2O5 content is 35.0 to 60.0%. The lower limit of the P2O5 content is preferably 40.0%, and more preferably 41.0%, 42.0%, 43.0%, 43.5%, and 45.5%, in that order. The upper limit of the P2O5 content is preferably 60.0%, and more preferably 58.0%, 56.0%, and 55.0%, in that order.
[0019] P2O5 is a glass network forming component, and is an essential component for containing a large amount of highly dispersive components in glass. By setting the content of P2O5 within the above range, an optical glass having excellent thermal stability and desired optical constants can be obtained. On the other hand, if the content of P2O5 is too low, the optical glass having the desired optical constants may not be obtained. Also, if the content of P2O5 is too high, the thermal stability of the glass may be deteriorated.
[0020] In the optical glass according to this embodiment, the mass ratio [B2O3 / P2O5] of the content of B2O3 to the content of P2O5 is 0.39 or less. The upper limit of this mass ratio is preferably 0.34, and more preferably 0.30, 0.27, and 0.25 in that order. The lower limit of this mass ratio is preferably 0.005, and more preferably 0.01, 0.015, and 0.02 in that order.
[0021] By setting the mass ratio [B2O3 / P2O5] within the above range, an optical glass having excellent thermal stability can be obtained. On the other hand, if the mass ratio is too large, the thermal stability of the glass may deteriorate.
[0022] In the optical glass according to this embodiment, the Na2O content is 5.0 to 40.0%. The lower limit of the Na2O content is preferably 10%, and more preferably 12.0%, 13.5%, 15.0%, 16.5%, 17.5%, and 18.0%, in that order. The upper limit of the Na2O content is preferably 30.0%, and more preferably 27.0%, 25.0%, and 23.0%, in that order.
[0023] Na2O has the function of improving the thermal stability and meltability of glass. By setting the content of Na2O within the above range, an optical glass having excellent thermal stability and meltability can be obtained. On the other hand, if the content of Na2O is too low, the thermal stability and meltability may decrease. Also, if the content of Na2O is too high, the thermal stability may decrease.
[0024] In the optical glass according to this embodiment, the content of BaO is 15.0% or less. The upper limit of the content of BaO is preferably 13.0%, more preferably 11.0%, 9.0%, and 7.0% in that order. The content of BaO is preferably as low as possible, and the lower limit is preferably 0%, more preferably 1.0%, 2.0%, and 3.0% in that order. The content of BaO may be 0%.
[0025] BaO is also a glass component that improves the thermal stability and devitrification resistance of the glass. By setting the content of BaO within the above range, an optical glass with excellent thermal stability and devitrification resistance can be obtained. On the other hand, if the content of BaO is too high, the high dispersion of the glass may be impaired, and the thermal stability and devitrification resistance of the glass may be reduced.
[0026] In the optical glass according to this embodiment, the total content of MgO, CaO, SrO and BaO [MgO+CaO+SrO+BaO] is 18.0% or less. The upper limit of the total content is preferably 16.0%, more preferably 14.0%, 12.0%, and 10.0% in that order. The lower the total content, the more preferable, and the lower limit is preferably 0%, more preferably 1.0%, 2.0%, and 3.0% in that order. The total content may be 0%.
[0027] By setting the total content [MgO+CaO+SrO+BaO] within the above range, it is possible to maintain thermal stability and resistance to devitrification without impeding high dispersion. On the other hand, if the total content is too large, the high dispersibility of the glass is impaired, and the thermal stability and resistance to devitrification of the glass may decrease.
[0028] In the optical glass according to this embodiment, the ZnO content is 15.0% or less. The upper limit of the ZnO content is preferably 13.0%, more preferably 11.0%, 9.0%, and 7.0% in that order. The lower the ZnO content, the more preferable, and the lower limit is preferably 0%, more preferably 1.0%, 2.0%, and 3.0% in that order. The ZnO content may be 0%.
[0029] By setting the ZnO content within the above range, the thermal stability of the glass can be improved, an increase in the specific gravity of the glass can be suppressed, and an optical glass having desired optical constants can be obtained.
[0030] In the optical glass according to this embodiment, the content of Nb2O5 is 25.0% or less. The upper limit of the content of Nb2O5 is preferably 20.0%, and more preferably 15.0%, 10.0%, 7.0%, and 5.0% in that order. The content of Nb2O5 is preferably as low as possible, and the lower limit is preferably 0%, and more preferably 1.0%, 2.0%, and 3.0% in that order. The content of Nb2O5 may be 0%.
[0031] Nb2O5 is a component that contributes to high refractive index and high dispersion. Therefore, by setting the content of Nb2O5 within the above range, an optical glass having the desired optical constants can be obtained. On the other hand, if the content of Nb2O5 is too high, the thermal stability of the glass may decrease and the coloring of the glass may become stronger.
[0032] In the optical glass according to this embodiment, the content of WO3 is 5.0% or less. The upper limit of the content of WO3 is preferably 4.5%, more preferably 4.0%, 3.5%, and 3.0% in that order. The content of WO3 is preferably low, and the lower limit is preferably 0%, more preferably 0.5%, 1.0%, and 1.5% in that order. The content of WO3 may be 0%.
[0033] By setting the WO3 content within the above range, the transmittance of the glass can be increased and an increase in the specific gravity of the glass can be suppressed.
[0034] In the optical glass according to this embodiment, the content of Bi2O3 is 10.0% or less. The upper limit of Bi2O3 is preferably 8.0%, more preferably 7.0%, 6.0%, and 5.0% in that order. The content of Bi2O3 is preferably as low as possible, and the lower limit is preferably 0%, more preferably 1.0%, 1.5%, and 2.0% in that order. The content of Bi2O3 may be 0%.
[0035] By setting the Bi2O3 content within the above range, the thermal stability of the glass can be improved and an increase in the specific gravity of the glass can be suppressed. On the other hand, if the Bi2O3 content is too high, the specific gravity increases and there is a risk of the glass becoming more colored.
[0036] In the optical glass according to this embodiment, the total content of TiO2, Nb2O5, WO3, Bi2O3 and Ta2O5 [TiO2+Nb2O5+WO3+Bi2O3+Ta2O5] is 3.0 to 30.0%. The lower limit of the total content is preferably 6.0%, more preferably 8.0%, 10.0%, and 12.0% in that order. The upper limit of the total content is preferably 29.0%, more preferably 27.0%, 25.0%, 22.0%, 20.0%, and 18.0% in that order.
[0037] TiO2, Nb2O5, WO3, Bi2O3 and Ta2O5 are components that contribute to high dispersion of glass. Therefore, by setting the total content [TiO2+Nb2O5+WO3+Bi2O3+Ta2O5] within the above range, optical glass with desired optical constants can be obtained. In addition, the thermal stability of the glass can be improved. On the other hand, if the total content is too high, optical glass with desired optical constants may not be obtained, and the thermal stability of the glass may decrease, causing the coloring of the glass to intensify.
[0038] In the optical glass according to this embodiment, the total content of TiO2, Nb2O5, WO3, Bi2O3, Ta2O5 and ZnO [TiO2+Nb2O5+WO3+Bi2O3+Ta2O5+ZnO] is 3.0 to 33.0%. The lower limit of the total content is preferably 6.0%, more preferably 8.0%, 10.0%, and 12.0% in that order. The upper limit of the total content is preferably 29.0%, more preferably 27.0%, 25.0%, 22.0%, 20.0%, and 18.0% in that order.
[0039] By setting the total content [TiO2+Nb2O5+WO3+Bi2O3+Ta2O5+ZnO] within the above range, an optical glass having the desired optical constants can be obtained. Also, the thermal stability of the glass can be improved. On the other hand, if the total content is too high, the optical glass having the desired optical constants may not be obtained, and the thermal stability of the glass may decrease, causing the coloring of the glass to become stronger.
[0040] Non-limiting examples of the contents and ratios of glass components other than those described above in the optical glass according to this embodiment are given below.
[0041] The upper limit of the mass ratio [(TiO2+Nb2O5+WO3+Bi2O3+Ta2O5) / (P2O5+B2O3+SiO2+Li2O+Na2O+K2O+Cs2O)] of the total content of TiO2, Nb2O5, WO3, Bi2O3 and Ta2O5 to the total content of P2O5, B2O3, SiO2, Li2O, Na2O, K2O and Cs2O is preferably 0.45, more preferably 0.43, 0.40, 0.37, 0.35, 0.33 in that order. The lower limit of the mass ratio is preferably 0.10, more preferably 0.12, 0.14, 0.15 in that order.
[0042] In order to obtain optical glass having desired optical constants, the mass ratio [(TiO2+Nb2O5+WO3+Bi2O3+Ta2O5) / (P2O5+B2O3+SiO2+Li2O+Na2O+K2O+Cs2O)] is preferably within the above range.
[0043] In the optical glass according to this embodiment, the lower limit of the mass ratio [TiO2 / (P2O5+B2O3)] of the content of TiO2 to the total content of P2O5 and B2O3 is preferably 0.10, more preferably 0.16, 0.21, and 0.24 in that order. The upper limit of the mass ratio is preferably 0.40, more preferably 0.37, 0.35, and 0.33 in that order.
[0044] Among the high refractive index, high dispersion components, TiO2 is a component that has a particularly large effect of increasing dispersion. However, if the content of TiO2 is large, the thermal stability and resistance to devitrification may decrease. Therefore, from the viewpoint of obtaining an optical glass that is highly dispersed and has excellent thermal stability and resistance to devitrification, it is preferable that the mass ratio [TiO2 / (P2O5+B2O3)] is within the above range.
[0045] In the optical glass according to this embodiment, the lower limit of the mass ratio [(P2O5+B2O3+SiO2) / (Li2O+Na2O+K2O+Cs2O)] of the total content of P2O5, B2O3 and SiO2 to the total content of Li2O, Na2O, K2O and Cs2O is preferably 0.80, more preferably 1.00, 1.20, 1.30 in that order. The upper limit of the mass ratio is preferably 2.60, more preferably 2.40, 2.20, 2.10 in that order.
[0046] From the viewpoint of obtaining an optical glass having excellent thermal stability, it is preferable that the mass ratio [(P2O5+B2O3+SiO2) / (Li2O+Na2O+K2O+Cs2O)] is within the above range.
[0047] In the optical glass according to this embodiment, the lower limit of the mass ratio [TiO2 / (TiO2+Nb2O5+WO3+Bi2O3+Ta2O5)] of the content of TiO2 to the total content of TiO2, Nb2O5, WO3, Bi2O3 and Ta2O5 is preferably 0.20, more preferably 0.30, 0.40, 0.50 in this order. The upper limit of the mass ratio is preferably 0.90, more preferably 0.80, 0.70, 0.60 in this order. The mass ratio may be 1.00.
[0048] Among the high refractive index, high dispersion components, TiO2 is a component that has a particularly large effect of increasing dispersion. Therefore, from the viewpoint of obtaining an optical glass having desired optical constants and excellent thermal stability and devitrification resistance, it is preferable that the mass ratio [TiO2 / (TiO2+Nb2O5+WO3+Bi2O3+Ta2O5)] is within the above range.
[0049] In the optical glass according to this embodiment, the lower limit of the mass ratio of the Na2O content to the K2O content [Na2O / K2O] is preferably 0.80, more preferably 1.00, 1.20, and 1.30 in that order, and the upper limit of this mass ratio is preferably 2.70, more preferably 2.50, 2.30, and 2.20 in that order.
[0050] From the viewpoint of improving the thermal stability and devitrification resistance of the glass, it is preferable that the mass ratio [Na2O / K2O] is in the above range. In particular, from the viewpoint of suppressing an excessive decrease in the refractive index and a decrease in chemical durability, it is preferable that the lower limit of the mass ratio is in the above range.
[0051] In the optical glass according to this embodiment, the upper limit of the Al2O3 content is preferably 15.0%, and more preferably 11.0%, 8.0%, and 6.0% in that order. The lower limit of the Al2O3 content is preferably 0%, and more preferably 0.5%, 1.0%, and 1.5% in that order. The Al2O3 content may be 0%.
[0052] From the viewpoint of suppressing a decrease in the devitrification resistance of the glass, the content of Al2O3 is preferably within the above range.
[0053] In the optical glass according to this embodiment, the upper limit of the SiO2 content is preferably 5.0%, and more preferably 4.0%, 3.0%, and 2.0% in that order. The lower limit of the SiO2 content is preferably 0%. The SiO2 content may be 0%.
[0054] SiO2 is a glass network forming component, and has the functions of improving the thermal stability, chemical durability, and weather resistance of glass, increasing the viscosity of molten glass, and making the molten glass easier to mold. On the other hand, if the SiO2 content is high, the devitrification resistance of glass tends to decrease. Therefore, from the viewpoint of improving the thermal stability and devitrification resistance of glass, the upper limit of the SiO2 content is preferably within the above range.
[0055] In addition, a quartz glass melting device such as a quartz glass crucible may be used to melt glass. In this case, a small amount of SiO2 is dissolved from the melting device into the glass melt, so even if the glass raw material does not contain SiO2, the produced glass contains a small amount of SiO2. The amount of SiO2 mixed into the glass from the quartz glass melting device depends on the melting conditions, but is, for example, about 0.5 to 1 mass% of the total content of all glass components. The content ratio of glass components other than SiO2 remains constant, and the amount of SiO2 increases by about 0.5 to 1 mass%. The above amount increases or decreases depending on the melting conditions. Since the optical properties such as the refractive index and Abbe number change depending on the content of SiO2, the content of glass components other than SiO2 is finely adjusted to obtain optical glass with desired optical properties.
[0056] In the optical glass according to this embodiment, the lower limit of the TiO2 content is preferably 0%, and more preferably 5.0%, 9.0%, and 12.0% in that order. The TiO2 content may be 0%. The upper limit of the TiO2 content is preferably 30.0%, and more preferably 25.0%, 21.0%, and 18.0% in that order.
[0057] TiO2 contributes greatly to high dispersion. On the other hand, TiO2 tends to increase the coloring of glass. In addition, TiO2 promotes the formation of crystals in the glass during the process of forming molten glass and slowly cooling it to obtain optical glass, thereby reducing the transparency of the glass (white turbidity). Therefore, the TiO2 content is preferably within the above range.
[0058] In the optical glass according to this embodiment, the upper limit of the Ta2O5 content is preferably 10.0%, and more preferably 5.0%, 3.0%, and 1.0% in that order. The lower limit of the Ta2O5 content is preferably 0%. The Ta2O5 content may be 0%.
[0059] Ta2O5 is a glass component that improves the thermal stability and devitrification resistance of glass. On the other hand, Ta2O5 increases the refractive index and makes the glass highly dispersible. In addition, when the content of Ta2O5 increases, the thermal stability of the glass decreases, and when the glass is melted, the glass raw material is likely to remain unmelted. Therefore, the content of Ta2O5 is preferably within the above range. Furthermore, Ta2O5 is an extremely expensive component compared to other glass components, and when the content of Ta2O5 increases, the production cost of the glass increases. Furthermore, since Ta2O5 has a larger molecular weight than other glass components, it may increase the specific gravity of the glass, which may result in an increase in the weight of the optical element.
[0060] In the optical glass according to this embodiment, the upper limit of the Li2O content is preferably 5%, and more preferably 3%, 2%, and 1% in that order. The lower limit of the Li2O content is preferably 0%. The Li2O content may be 0%.
[0061] Li2O has the function of lowering the glass transition temperature Tg. On the other hand, if the content of Li2O is large, the acid resistance decreases. Therefore, the content of Li2O is preferably within the above range.
[0062] In the optical glass according to this embodiment, the upper limit of the total content of Li2O, Na2O and K2O [Li2O+Na2O+K2O] is preferably 45.0%, more preferably 42.0%, 39.0% and 37.0%, in that order. The lower limit of the total content is preferably 10.0%, more preferably 15.0%, 19.0% and 22.0%, in that order.
[0063] Li2O, Na2O and K2O all have the function of improving the thermal stability of glass. However, if their contents increase, chemical durability and weather resistance decrease. Therefore, it is preferable that the total content of Li2O, Na2O and K2O [Li2O + Na2O + K2O] is within the above range.
[0064] In the optical glass according to this embodiment, the upper limit of the Cs2O content is preferably 5%, and more preferably 3%, 2%, and 1% in that order. The lower limit of the Cs2O content is preferably 0%. The Cs2O content may be 0%.
[0065] Although Cs2O has the function of improving the thermal stability of glass, if the content is high, the thermal stability, chemical durability, and weather resistance of the glass decrease, so the content of Cs2O is preferably within the above range.
[0066] In the optical glass according to this embodiment, the upper limit of the MgO content is preferably 10.0%, and more preferably 8.0%, 7.0%, 6.0%, and 5.0%, in that order. The lower limit of the MgO content is preferably 0%. The MgO content may be 0%.
[0067] In the optical glass according to this embodiment, the upper limit of the CaO content is preferably 10.0%, and more preferably 8.0%, 7.0%, 6.0%, and 5%, in that order. The lower limit of the CaO content is preferably 0%. The CaO content may be 0%.
[0068] In the optical glass according to this embodiment, the upper limit of the SrO content is preferably 10.0%, and more preferably 8.0%, 7.0%, 6.0%, and 5.0%, in that order. The lower limit of the SrO content is preferably 0%. The SrO content may be 0%.
[0069] MgO, CaO, SrO, and BaO are glass components that improve the thermal stability and devitrification resistance of glass. However, if the content of these glass components is high, the high dispersibility is impaired and the thermal stability and devitrification resistance of glass are reduced. Therefore, it is preferable that the content of each of these glass components is within the above-mentioned range.
[0070] In the optical glass according to this embodiment, the upper limit of the ZrO2 content is preferably 10.0%, and more preferably 8.0%, 7.0%, 6.0%, and 5.0%, in that order. The lower limit of the ZrO2 content is preferably 0%. The ZrO2 content may be 0%.
[0071] ZrO2 is a glass component that improves the thermal stability and devitrification resistance of glass. However, if the content of ZrO2 is too high, the thermal stability tends to decrease. Therefore, from the viewpoint of maintaining the thermal stability and devitrification resistance of glass well, the content of ZrO2 is preferably within the above range.
[0072] In the optical glass according to this embodiment, the upper limit of the Sc2O3 content is preferably 2%, and the lower limit of the Sc2O3 content is preferably 0%.
[0073] In the optical glass according to this embodiment, the upper limit of the HfO2 content is preferably 2%. Also, the lower limit of the HfO2 content is preferably 0%.
[0074] Both Sc2O3 and HfO2 have the function of increasing the refractive index nd and are expensive components, so the respective contents of Sc2O3 and HfO2 are preferably within the above ranges.
[0075] In the optical glass according to this embodiment, the upper limit of the Lu2O3 content is preferably 2%, and the lower limit of the Lu2O3 content is preferably 0%.
[0076] Lu2O3 has the function of increasing the refractive index nd. In addition, since it has a large molecular weight, it is also a glass component that increases the specific gravity of the glass. Therefore, the content of Lu2O3 is preferably within the above range.
[0077] In the optical glass according to this embodiment, the upper limit of the GeO2 content is preferably 2%. Also, the lower limit of the GeO2 content is preferably 0%.
[0078] GeO2 has the function of increasing the refractive index nd, and is an extremely expensive component among commonly used glass components. Therefore, from the viewpoint of reducing the manufacturing cost of the glass, the content of GeO2 is preferably in the above range.
[0079] In the optical glass according to this embodiment, the upper limit of the La2O3 content is preferably 10.0%, and more preferably 8.0%, 7.0%, 6.0%, and 5.0%, in that order. The lower limit of the La2O3 content is preferably 0%. The La2O3 content may be 0%.
[0080] If the content of La2O3 is large, the thermal stability and devitrification resistance of the glass decrease, and the glass becomes more susceptible to devitrification during production. Therefore, from the viewpoint of suppressing the decrease in thermal stability and devitrification resistance, the content of La2O3 is preferably within the above range.
[0081] In the optical glass according to this embodiment, the upper limit of the Gd2O3 content is preferably 10.0%, and more preferably 8.0%, 7.0%, 6.0%, and 5.0%, in that order. The lower limit of the Gd2O3 content is preferably 0%.
[0082] If the content of Gd2O3 is too high, the thermal stability and devitrification resistance of the glass are reduced, and the glass is easily devitrified during production. If the content of Gd2O3 is too high, the specific gravity of the glass increases, which is not preferable. Therefore, from the viewpoint of suppressing the increase in specific gravity while maintaining the thermal stability and devitrification resistance of the glass in a good condition, the content of Gd2O3 is preferably within the above range.
[0083] In the optical glass according to this embodiment, the upper limit of the Y2O3 content is preferably 10.0%, and more preferably 8.0%, 7.0%, 6.0%, and 5.0%, in that order. The lower limit of the Y2O3 content is preferably 0%. The Y2O3 content may be 0%.
[0084] If the content of Y2O3 is too high, the thermal stability and resistance to devitrification of the glass decrease. Therefore, from the viewpoint of suppressing the decrease in the thermal stability and resistance to devitrification, the content of Y2O3 is preferably within the above range.
[0085] In the optical glass according to this embodiment, the upper limit of the Yb2O3 content is preferably 2%, and the lower limit of the Yb2O3 content is preferably 0%.
[0086] Yb2O3 has a larger molecular weight than La2O3, Gd2O3, and Y2O3, and therefore increases the specific gravity of the glass. When the specific gravity of the glass increases, the mass of the optical element increases. For example, when a lens with a large mass is incorporated into an autofocus imaging lens, the power required to drive the lens during autofocus increases, causing rapid battery consumption. Therefore, it is desirable to reduce the Yb2O3 content and suppress the increase in the specific gravity of the glass.
[0087] Moreover, if the content of Yb2O3 is too high, the thermal stability and devitrification resistance of the glass are reduced. From the viewpoint of preventing a decrease in the thermal stability of the glass and suppressing an increase in the specific gravity, the content of Yb2O3 is preferably within the above range.
[0088] The optical glass according to this embodiment is preferably composed mainly of the above-mentioned glass components, namely, B2O3, K2O, P2O5, and Na2O as essential components and ZnO, Nb2O5, WO3, Bi2O3, Al2O3, SiO2, TiO2, Ta2O5, Li2O, Cs2O, MgO, CaO, SrO, BaO, ZrO2, Sc2O3, HfO2, Lu2O3, GeO2, La2O3, Gd2O3, Y2O3, and Yb2O3 as optional components, and the total content of the above-mentioned glass components is preferably 95% or more, more preferably 98% or more, even more preferably 99% or more, and even more preferably 99.5% or more.
[0089] In the optical glass according to this embodiment, the upper limit of the TeO2 content is preferably 2%, and the lower limit of the TeO2 content is preferably 0%.
[0090] Since TeO2 is toxic, it is preferable to reduce the content of TeO2, and therefore the content of TeO2 is preferably within the above range.
[0091] The optical glass according to this embodiment is preferably composed essentially of the above glass components, but may contain other components as long as they do not impair the effects of the present invention. Furthermore, the present invention does not exclude the inclusion of unavoidable impurities.
[0092] <Other ingredient composition> Pb, As, Cd, Tl, Be, and Se are all toxic, so it is preferable that the optical glass according to this embodiment does not contain these elements as glass components.
[0093] U, Th, and Ra are all radioactive elements, and therefore it is preferable that the optical glass according to this embodiment does not contain these elements as glass components.
[0094] V, Cr, Mn, Fe, Co, Ni, Cu, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, and Tm increase the coloring of the glass and can be sources of fluorescence, so it is preferable that the optical glass according to this embodiment does not contain these elements as glass components.
[0095] Sb (Sb2O3), Sn (SnO2), and Ce (CeO2) are optional elements that function as clarifiers. Of these, Sb (Sb2O3) is a clarifier with a large clarification effect. However, Sb (Sb2O3) has a strong oxidizing property, and if the amount of Sb (Sb2O3) added is increased, the Sb (Sb2O3) contained in the glass oxidizes the molding surface of the press mold during precision press molding. Therefore, as precision press molding is repeated, the molding surface deteriorates significantly, making precision press molding impossible. In addition, the surface quality of the molded optical element decreases. In addition, Sn (SnO2) and Ce (CeO2) have a smaller clarification effect than Sb (Sb2O3). Furthermore, if a large amount of Ce (CeO2) is added, the coloring of the glass becomes stronger. Therefore, when a clarifier is added, it is preferable to add Sb (Sb2O3) while paying attention to the amount added.
[0096] The contents of the fining agents described below are expressed in terms of oxides. The content of Sb2O3 is expressed as an exclusive percentage. That is, when the total content of all glass components other than Sb2O3, SnO2, and CeO2 is taken as 100 mass%, the content of Sb2O3 is preferably 1 mass% or less, and more preferably 0.2 mass% or less, 0.05 mass% or less, 0.02 mass% or less, and 0.01 mass% or less in that order. The content of Sb2O3 may be 0 mass%.
[0097] The content of SnO2 is also expressed as an exclusive ratio. That is, when the total content of all glass components other than SnO2, Sb2O3 and CeO2 is taken as 100 mass%, the content of SnO2 is preferably 1 mass% or less, more preferably 0.2 mass% or less, and further preferably 0.02 mass% or less. The content of SnO2 may be 0 mass%, and it is preferable that SnO2 is substantially not contained. By setting the content of SnO2 in the above range, the clarity of the glass can be improved.
[0098] The content of CeO2 is also expressed as an exclusive ratio. That is, when the total content of all glass components other than CeO2, Sb2O3, and SnO2 is taken as 100 mass%, the content of CeO2 is preferably 1 mass% or less, more preferably 0.2 mass% or less, and even more preferably 0.02 mass% or less. The content of CeO2 may be 0 mass%, and it is preferable that CeO2 is substantially not contained. By setting the content of CeO2 in the above range, the clarity of the glass can be improved.
[0099] (Glass properties) <Refractive index nd> In the optical glass according to this embodiment, the refractive index nd is preferably in the range of 1.55 to 1.68, and may further be in the range of 1.55 to 1.65, or 1.57 to 1.64.
[0100] The refractive index nd can be adjusted to a desired value by appropriately adjusting the content of each glass component. Components that act to relatively increase the refractive index nd (high refractive index components) include Nb2O5, TiO2, WO3, Bi2O3, Ta2O5, ZrO2, La2O3, etc. On the other hand, components that act to relatively decrease the refractive index nd (low refractive index components) include P2O5, SiO2, B2O3, Li2O, Na2O, K2O, etc. Therefore, the refractive index nd can be increased by increasing the mass ratio of the total content of TiO2, Nb2O5, WO3, Bi2O3, and Ta2O5 to the total content of P2O5, B2O3, SiO2, Li2O, Na2O, K2O, and Cs2O [(TiO2+Nb2O5+WO3+Bi2O3+Ta2O5) / (P2O5+B2O3+SiO2+Li2O+Na2O+K2O+Cs2O)], and the refractive index nd can be decreased by decreasing this mass ratio.
[0101] <Abbe number νd> In the optical glass according to this embodiment, the Abbe number vd is preferably 25-50, and more preferably 28-45.
[0102] The Abbe number νd can be adjusted to a desired value by appropriately adjusting the content of each glass component. Components that relatively lower the Abbe number νd, i.e., high dispersion components, are Nb2O5, TiO2, WO3, Bi2O3, Ta2O5, ZrO2, etc. On the other hand, components that relatively increase the Abbe number νd, i.e., low dispersion components, are P2O5, SiO2, B2O3, Li2O, Na2O, K2O, La2O3, BaO, CaO, SrO, etc.
[0103] <Specific gravity of glass> In the optical glass according to this embodiment, the specific gravity is preferably 3.20 or less, more preferably 3.10 or less, and more preferably 2.95 or less. There is no particular lower limit to the specific gravity, but it is usually 2.50. If the specific gravity of the glass can be reduced, the weight of the lens can be reduced. As a result, the power consumption of the autofocus drive of the camera lens equipped with the lens can be reduced.
[0104] <Glass transition temperature Tg> The glass transition temperature Tg of the optical glass according to this embodiment is preferably 520° C. or lower, and more preferably 500° C. or lower, 480° C. or lower, and 470° C. or lower in that order. The lower limit of the glass transition temperature Tg is usually 300° C., and preferably 350° C.
[0105] By setting the upper limit of the glass transition temperature Tg within the above range, it is possible to suppress increases in the molding temperature and annealing temperature of the glass, thereby reducing thermal damage to press molding equipment and annealing equipment. Also, by setting the lower limit of the glass transition temperature Tg within the above range, it becomes easier to maintain the thermal stability of the glass well while maintaining the desired Abbe number and refractive index.
[0106] <Light transmittance of glass> The light transmittance of the optical glass according to this embodiment can be evaluated by the coloring degree λ5. The spectral transmittance of a glass sample having a thickness of 10.0 mm±0.1 mm is measured in the wavelength range of 200 to 700 nm, and the wavelength at which the external transmittance becomes 5% is defined as λ5.
[0107] The λ5 of the optical glass according to this embodiment is preferably 390 nm or less, more preferably 380 nm or less, and further preferably 375 nm or less.
[0108] By using optical glass in which λ5 is shortened, it is possible to provide an optical element that enables suitable color reproduction.
[0109] <Average linear expansion coefficient α 100-300 > In the optical glass according to this embodiment, the average linear expansion coefficient α 100-300 The lower limit is preferably 100×10 -7 ℃ -1 and even 120×10 -7 ℃ -1 , 130×10 -7 ℃ -1 , 140× 10 -7 ℃ -1 In addition, the average linear expansion coefficient α 100-300 The upper limit of is 210×10 from the viewpoint of maintaining the stability of the glass and obtaining the desired optical properties. -7 ℃ -1 can be exemplified, and preferably 205×10 -7 ℃ -1 and even 200×10 -7 ℃ -1 , 195×10 -7 ℃ -1 , 190×10 -7 ℃ -1 The order of preference is:
[0110] Average linear expansion coefficient α 100-300 The average linear expansion coefficient α is measured in accordance with the JOGIS08-2019 standard. The sample is a round bar with a length of 20 mm ± 0.5 mm and a diameter of 5 mm ± 0.5 mm. With a load of 98 mN applied to the sample, it is heated at a constant rate of 4°C per minute, and the temperature and the elongation of the sample are measured in 1-second intervals. 100-300 is the average value of the linear expansion coefficient at 100 to 300°C. In this specification, the average linear expansion coefficient α is defined as [°C -1], but the unit is [K -1 ], the value of the average linear expansion coefficient α is the same.
[0111] (Optical glass manufacturing) The optical glass according to the embodiment of the present invention may be produced by blending glass raw materials to obtain the above-mentioned predetermined composition, and using the blended glass raw materials according to a known glass manufacturing method. For example, a plurality of compounds may be blended and thoroughly mixed to obtain a batch raw material, and the batch raw material may be placed in a quartz crucible or a platinum crucible to be roughly melted (rough melt). The molten material obtained by the rough melting is quenched and crushed to produce cullet. The cullet is then placed in a platinum crucible, heated and remelted (remelt) to obtain a molten glass, which is then clarified and homogenized, molded, and slowly cooled to obtain an optical glass. A known method may be applied to the molding and slow cooling of the molten glass.
[0112] In addition, as long as a desired glass component can be introduced into the glass in a desired content, the compound used when preparing the batch raw materials is not particularly limited. Examples of such compounds include oxides, carbonates, nitrates, hydroxides, fluorides, etc.
[0113] (Manufacturing of optical elements, etc.) To manufacture an optical element using the optical glass according to the embodiment of the present invention, a known method may be applied. For example, glass raw materials are melted to form molten glass, and the molten glass is poured into a mold and molded into a plate shape to manufacture a glass material made of the optical glass according to the present invention. The obtained glass material is appropriately cut, ground, and polished to manufacture cut pieces of a size and shape suitable for press molding. The cut pieces are heated and softened, and press molded (reheat pressed) by a known method to manufacture an optical element blank that is similar to the shape of the optical element. The optical element blank is annealed, and then ground and polished by a known method to manufacture an optical element.
[0114] The optically functional surface of the prepared optical element may be coated with an anti-reflection film, a total reflection film, or the like depending on the intended use.
[0115] Examples of optical elements include various lenses such as spherical lenses, prisms, and diffraction gratings.
[0116] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.
[0117] (Example) [Preparation of glass samples] In order to obtain glass having the compositions of Samples No. 1 to 32 shown in Tables 1(1) and 1(2), the compound raw materials corresponding to each component, i.e., raw materials such as phosphates, carbonates, and oxides, were weighed and thoroughly mixed to obtain a blended raw material. The blended raw materials were placed in a platinum crucible, heated to 900 to 1350°C in an air atmosphere to melt, and homogenized and clarified by stirring to obtain a molten glass. The molten glass was cast into a mold to be shaped, and slowly cooled to obtain a block-shaped glass sample. Alternatively, the raw materials may be charged into a quartz glass crucible, melted, transferred to a platinum crucible, and further heated to melt, homogenized by stirring, and the molten glass obtained by clarification may be poured into a mold and shaped, followed by slow cooling.
[0118] [Glass sample evaluation] The glass composition, specific gravity, refractive index nd, Abbe number νd, λ5, glass transition temperature Tg, and average linear expansion coefficient α of the obtained glass sample were measured by the following methods. 100-300 The results are shown in Table 2(1) and (2).
[0119] [1] Glass composition The content of each glass component in the obtained glass sample was measured by inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0120] [2] Specific gravity Measurements were made based on the Japan Optical Glass Industry Association standard JOGIS-05.
[0121] [3] Refractive index nd and Abbe number νd Measurements were made based on the Japan Optical Glass Industry Association standard JOGIS-01.
[0122] [4] λ5 A glass sample was processed to have a thickness of 10 mm and parallel optically polished flat surfaces, and the spectral transmittance was measured in the wavelength range from 280 nm to 700 nm. The intensity of the light beam perpendicularly incident on one of the optically polished flat surfaces was defined as intensity A, and the intensity of the light beam emerging from the other flat surface was defined as intensity B, and the spectral transmittance B / A was calculated. The wavelength at which the spectral transmittance was 5% was defined as λ5. Note that the spectral transmittance also includes the reflection loss of the light beam on the sample surface.
[0123] [5] Glass transition temperature Tg The glass transition temperature Tg was determined based on a DSC chart obtained by heating the solid-state glass using a differential scanning calorimeter DSC3300SA (NETZSCH Japan).
[0124] [6] Average linear expansion coefficient α 100-300 The average linear expansion coefficient of the obtained glass samples was measured with reference to the provisions of JOGIS08-2019. The average linear expansion coefficient was measured using a thermomechanical analyzer TMA4000SE (NETZSCH Japan). The sample was a round bar with a length of 20 mm ± 0.5 mm and a diameter of 5 mm ± 0.5 mm. During the measurement, a load of 98 mN was applied to the sample, and the temperature and the elongation of the sample were measured every second while the temperature was raised at a constant rate of 4°C per minute. The average value of the linear expansion coefficient at 100 to 300°C was taken as the average linear expansion coefficient α 100-300 It was decided.
[0125] [7] Devitrification resistance The obtained glass samples were examined using an optical microscope to check for the presence or absence of crystals or turbidity. The magnification of the optical microscope was 10 to 100 times. When neither crystals nor turbidity was observed inside the glass, it was judged as "good", and when at least one of crystals and turbidity was observed, it was judged as "poor". All of Samples No. 1 to 32 of the examples were judged as "good". Samples No. 1 to 32 of the examples were confirmed to be glasses with excellent resistance to devitrification.
[0126] [Table 1(1)]
[0127] [Table 1(2)]
[0128] [Table 2(1)]
[0129] [Table 2(2)]
[0130] Example 2 The glass sample obtained in Example 1 was cut and ground to prepare cut pieces. The cut pieces were press molded by a reheat press to prepare optical element blanks. The optical element blanks were precisely annealed to precisely adjust the refractive index to a required refractive index, and then ground and polished by a known method to obtain various lenses such as biconvex lenses, biconcave lenses, planoconvex lenses, planoconcave lenses, concave meniscus lenses, and convex meniscus lenses.
[0131] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims.
[0132] For example, by adjusting the composition as described in the specification to the glass compositions exemplified above, an optical glass according to one aspect of the present invention can be produced. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.
Claims
1. B as glass component 2 O 3 and K. 2 Contains O, P 2 O 5 The content is 43.5 to 60.0 mass %, B 2 O 3 Content and P 2 O 5 The mass ratio of the content of [B 2 O 3 / P 2 O 5 ] is 0.39 or less, Na 2 The content of O is 5.0 to 40.0 mass %, The content of BaO is 15.0 mass% or less, The total content of MgO, CaO, SrO and BaO [MgO + CaO + SrO + BaO] is 18.0 mass% or less, The ZnO content is 15.0 mass% or less, Nb 2 O 5 The content is 25.0 mass% or less, WO 3 The content is 5.0 mass% or less, Bi 2 O 3 The content is 10.0 mass% or less, Li 2 The content of O is 1 mass% or less, T 2 O 5 The content is 1.0 mass% or less, Na 2 O content and K content 2 Mass ratio of Na 2 O / K 2 O] is 1.30 to 2.70, TiO 2 , Nb 2 O 5 , W.O. 3 , Bi 2 O 3 and Ta 2 O 5 The total content [TiO 2 +Nb 2 O 5 +W.O. 3 +Bi 2 O 3 +Ta 2 O 5 ] is 3.0 to 30.0 mass %, TiO 2 , Nb 2 O 5 , W.O. 3 , Bi 2 O 3 , Ta 2 O 5 and the total content of ZnO [TiO 2 +Nb 2 O 5 +W.O. 3 +Bi 2 O 3 +Ta 2 O 5 +ZnO] is 3.0 to 33.0 mass %, Satisfy one or more of the following (i) and (ii): (i) The content of Nb 2 O 5 is 1.0 mass % or more. (ii) The TiO 2 content is 5.0 mass % or more. An optical glass that is substantially free of Pb.
2. 2. The optical glass according to claim 1, wherein the combined content of MgO, CaO, SrO and BaO [MgO + CaO + SrO + BaO] is 3.04 mass % or less.
3. 3. An optical element comprising the optical glass according to claim 1 or 2.
Citation Information
Patent Citations
JP1971003462B
Projecting device
JP1983025607A
Phosphate optical glass
JP1994016450A
Optical glass and optical element
JP2005053743A
Optical glass, lens preform and optical element
JP2016074581A
